2018
DOI: 10.1149/2.0521805jes
|View full text |Cite
|
Sign up to set email alerts
|

Communication—Reactive Sintering of a CoFe2O4Coating on Ferritic Stainless Steels for SOFC Interconnect Application

Abstract: A mixed Fe+CoO precursor was successfully utilized to synthesize a dense CoFe 2 O 4 spinel coating on the Crofer 22 APU interconnect via reactive sintering at 900 • C for 2 h in air without the use of any reduction treatment. Both the uncoated and coated samples were subject to thermal oxidation at 850 • C for 500 h in air. Phase constituents, microstructure, and area specific resistance (ASR) of the uncoated and coated samples before and after the oxidation testing were evaluated. The CoFe 2 O 4 layer effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Furthermore, while the sinterability of the spinels is normally poor, an innovative approach has been identified to dramatically lower their sintering temperature to close to the stack firing/operating temperatures, making the utilization of spinel-based contact materials an appealing alternative to the conductive perovskites. 14,58…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while the sinterability of the spinels is normally poor, an innovative approach has been identified to dramatically lower their sintering temperature to close to the stack firing/operating temperatures, making the utilization of spinel-based contact materials an appealing alternative to the conductive perovskites. 14,58…”
Section: Discussionmentioning
confidence: 99%
“…Different systems of binary spinels, including Mn-Co, Ni-Co, Ni-Fe, and Cu-Mn, have been evaluated and investigated as contact materials in previous reports [12][13][14][15]. The spinels typically possess reasonable conductivity and excellent Cr-blocking ability [16][17][18][19][20][21]. Furthermore, it has been demonstrated that the modification of the spinel by adding different dopants can contribute to better performance, such as electrical conductivity and CTE [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…1,7,8 One of the key concerns for spinelbased contact is their poor sinterability, which could be addressed via the utilization of an environmentally-assisted reactive sintering mechanism with at least one metal-containing powder in the contact precursor layer. 1,[7][8][9][10] Despite having excellent static long-term stability, the performance of SOFC decays rapidly in thermal shock due to its multilayered feature, thus restricting its application as auxiliary power supplies where frequent, rapid thermal cycling is expected. Even in stationary application, SOFC experiences cooling and restarting for hot standby, emergencies such as unexpected interruption of gas supply and partial maintenance, which could lead to thermal stress generation and subsequent stack durability concerns.…”
mentioning
confidence: 99%